2005
DOI: 10.1007/s00428-005-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal alterations in early stages of malignant mesotheliomas

Abstract: In a case of a 67-year-old man with two different early stages of a predominantly epithelioid mesothelioma ("mesothelioma in situ", "early-stage mesothelioma"), chromosomal imbalances were determined by comparative genomic hybridisation (CGH), a molecular cytogenetic technique to detect chromosomal gains and losses in tumour cells. In the case of the mesothelioma in situ cells, nine different chromosomal alterations could be detected (losses on 3p, 5q, 6q, 8p, 9p, 15q, 22q, Y; gain on 7q), whereas the early-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…As noted in the Introduction, the diagnosis of MIS is considered unreliable by routine histological examination, and most of the cases that have been claimed to show MIS have been in the setting of a co-existing invasive mesothelioma. To our knowledge, the only study that has attempted to look at genomic events in a case of possible MIS is that of Simon et al, 9 who used comparative genomic hybridisation and reported an almost identical set of chromosomal losses in both the surface and invasive component of a mesothelioma. However, the problem with all these studies is that there is no proof that the surface proliferation really represents primary in-situ disease rather than surface spread of invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the Introduction, the diagnosis of MIS is considered unreliable by routine histological examination, and most of the cases that have been claimed to show MIS have been in the setting of a co-existing invasive mesothelioma. To our knowledge, the only study that has attempted to look at genomic events in a case of possible MIS is that of Simon et al, 9 who used comparative genomic hybridisation and reported an almost identical set of chromosomal losses in both the surface and invasive component of a mesothelioma. However, the problem with all these studies is that there is no proof that the surface proliferation really represents primary in-situ disease rather than surface spread of invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Overlap exists between the different categories, and there is some argument that CIS is different at a molecular level from high grade dysplasia and may clinically behave differently, but this may need confirmation by further studies. 17,20,40,47 In addition, telomerase dysregulation and hypermethylation are intermediate steps, whilst p53 and KRAS mutations occur later in the development of invasive lesions (reviewed in 13,15,16). Others have found that the degree of dysplasia at baseline-assessment was not predictive of patient outcome, and indeed, molecular signature of the lesion may be more predictive of its behaviour than histological grade.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…6) and reliable and early diagnosis of mesothelioma in situ would in theory facilitate curative therapy. 17 Features that have been proposed as criteria for diagnosis of in situ mesothelioma include a single layer of atypical mesothelial cells along the pleural surface, as well as complex multilayered collections of mesothelial cells along the pleural surface, either as solid sheets or papillary structures. However, Simon et al did report a single case of mesothelioma in situ in association with focal early-stage invasive mesothelioma and both the in situ lesion and the invasive mesothelioma showed a very similar though not identical profile of chromosomal abnormalities, and we commonly see foci of in situ mesothelial atypia in sections that also contain invasive tumour.…”
Section: In Situ Mesotheliomamentioning
confidence: 99%
See 2 more Smart Citations